Targeting miRNAs with anesthetics in cancer: Current understanding and future perspectives - Peyman Tabnak (Elsevier, 2021)
Anesthetics are extensively used during cancer surgeries. The progression of cancer can be influenced by perioperative events such as exposure to general or local anesthesia. However, whether they inhibit cancer or act as a causative factor for metastasis and exert deleterious effects on cancer growth differs based on the type of cancer and the therapy administration. Recent experimental data suggested that many of the most commonly used anesthetics in surgical oncology, whether general or local agents, can alter gene expression and cause epigenetic changes via modulating miRNAs. miRNAs are single-stranded non-coding RNAs that regulate gene expression at various levels, and their dysregulation contributes to the pathogenesis of cancers. However, anesthetics via regulating miRNAs can concurrently target several effectors of cellular signaling pathways involved in cell differentiation, proliferation, and viability. This review summarized the current research about the effects of different anesthetics in regulating cancer, with a particular emphasis on the role of miRNAs. A significant number of studies conducted in this area of research illuminate the effects of anesthetics on the regulation of miRNA expression; therefore, we hope that a thorough understanding of the underlying mechanisms involved in the regulation of miRNA in the context of anesthesia-induced cancer regulation could help to define optimal anesthetic regimens and provide better perspectives for further studies.